Development Of Analytical Methods and Validation of Amlodipine, Hydrochlorthiazide and Telmisartan by Rp-HPLC Method - Mrs. Pritam Khandave, Dr. Narendra Gowekar, Dr. Vikas Jain (International Journal of Advanced Science and Technology, 2019)
The aim of this research work was develop simple, precise and rapid RP-HPLC Method of analysis of Tenofovir, Lamivudine and Efavirenz in bulk and pharmaceutical dosage form. RP-HPLC method was developed for the estimation of amlodipine, hydrochlorthiazide and telmisartan in tablet dosage form with the help of HPLC approaches. The proposed methods were applied for the determination of drug in tablet dosage form. A rapid and reliable RP-HPLC method was developed and validated estimation of amlodipine, hydrochlorthiazide and telmisartan, in tablet dosage form. The RP-HPLC method was performed C18-(100mm x 4.6 mm,) 2.5 & C18-(250mm x 4.6 mm,) 5.0 μm particle size in gradient mode, and the sample was analysed using DMSO and pH buffer (0.05% OPA with TEA) as a mobile phase for amlodipine, hydrochlorthiazide and telmisartan 70:30ml, 0.7 ml flow by the retention time for amlodipine, hydrochlorthiazide and telmisartan found 3.704,6.054 and 7.686 min respectively. The method was applied to marketed tablet formulations. The tablet assay was performed for combination was validated for accuracy, precision, linearity, specificity, and sensitivity in accordance with ICH guidelines. Validation related the method is specific, rapid, accurate, precise, reliable, and reproducible. Calibration plots by HPLC were linear over 54-20µg/ml for Amlodipine, 10-50 µg/ml for Hydrochlorothiazide and 32-160 µg/ml for Telmisartan. The method can be used for routine of the quality control in pharmaceuticals. The RP-HPLC method was found to be simple, economical and rapid as compared to MS method was found to be more accurate, precise and robust. Both these methods can be used for routine analysis of AMLO, TELMI and HCZ in tablet dosage form.